Determinan Nilai Perusahaan di Sektor Kesehatan: Peran Moderasi Kebijakan Dividen pada Perusahaan Tercatat BEI (2020–2024) - Nanda Suryadi; Yayu Kusdiana; Arie Yunelly; Sulaiman Musa (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2026)
This study is motivated by the observed decline in average share prices among healthcare sector companies listed on the Indonesia Stock Exchange between 2020 and 2024, indicating an overall weakening of firm value. The research aims to examine and analyze the extent to which profitability, firm size, leverage, and insider ownership influence firm value, with dividend policy serving as a moderating variable. A quantitative approach is employed, grounded in Signaling Theory and Agency Theory. The sample was selected using purposive sampling, resulting in eight healthcare sector companies and a total of 40 observation units. Data were sourced from the companies' annual financial reports and analyzed using panel data regression with the Fixed Effect Model (FEM) approach, utilizing EViews software. The findings reveal that profitability has a positive and significant effect on firm value, whereas firm size and leverage do not show a significant influence. Conversely, insider ownership is found to have a negative effect on firm value. While dividend policy does not moderate the relationships between profitability, firm size, or leverage and firm value, it is shown to strengthen the influence of insider ownership on firm value. An Adjusted R-Squared coefficient of 87.9% indicates that the developed model possesses high explanatory power regarding the variation in firm value.